Ooó do vovô: entremeios de imagem e palavra na correspondência desenhada de João Guimarães Rosa - Furtado, Victor Silva Morais (2024)
Since humanity has been self perceived, it has guided itself through images. Adopting different formats, the image is not only a medium, but also a method, its own way of thinking about communication processes. Drawing, an act that connects the action of imagining to the movement of the body to produce graphics, has also been with us for centuries, as it is a gesture that fits into the production of images. This production of images through drawing was something present in João Guimarães Rosa's writing method. Through the shapes he drew in his travel notebooks, Rosa took drawing as a procedural part of his writing. Drawing was a form of reminiscence and literary inspiration. Because of this, there is a vast number of academic works that deal with Rosa's drawings as a fundamental part of the genesis of his textual body of work. However, a little-studied correspondence presents Guimarães Rosa's act of drawing in a unique point of view. Between 1966 and 1967, Rosa sent a series of postcards to his then wife Aracy's granddaughters, Vera and Beatriz Helena Tess. Because they were still very young, the girls couldn't read, so grandpa Joãozinho communicated his feelings to them through the drawings he sent them in the mail. In Ooó do vovô: Correspondência de João Guimarães Rosa, vovô Joãozinho, com Vera e Beatriz Helena Tess, a 2003 book that compiles this correspondence, we see Rosa’s drawings that operate not only by playing with words, but also by seeing them from the perspective of the world of children. Through lexical exercises, Rosa established an imagetic writing, a way of articulating the peculiar relationship she had with her granddaughters. The book in question is analyzed by this work as an editorial design process that takes forward the amalgamated aspects of image and writing of postcards, now transposed into book format by means of a double intersemiotic translation. If Guimarães Rosa used to draw as a way of translating writings to his granddaughters, now this same writing is translated ‒ transcreated ‒ into a book, in a process of conversation between the writer and the graphic design. At the end of the work, the graphics of the aforementioned correspondence from Rosa are analyzed using graphic design resources, establishing an interweaving of writing and image in the analytical elaboration of this work.